Correlation of cyclin D1 between hormones receptors and other clinical parameters in invasive breast carcinoma - Singh, Seema; Mabood, Abdul; Dwivedi, Neetu; Alam, M. Qamar; Gangwar, Abhinav (International Journal of Research in Medical Sciences, 2020)
Background: Breast carcinoma is the most common malignancy in women. The prognosis of breast carcinoma is determined by different prognostic factors including age of patients, type of tumour, stage of tumours, grade of tumors, presence or absence of metastasis and hormones receptor status. The present study was conducted to assess the expression of cyclin D1 in invasive breast carcinoma and its correlation with age, tumour grade, lymph node metastasis and hormones receptors (estrogen receptors and progesterone receptors). Methods: Present study was conducted in department of pathology UPUMS, Saifai, Etawah, Uttar Pradesh. This was a prospective cross sectional observation study conducted on 21 mastectomy specimen from January 2019 to June 2020, diagnosed as invasive breast carcinoma on routine haematoxylin and eosin stain. Immunohistochemistery marker was scored by using allred scoring methods. Grading was calculated according to Nottingham grading system. Results: It was observed out of 21 cases 9 (42.8%) cases were showing cyclin D1 positivity. In our study 14 cases were estrogen receptor and progesterone receptor positive, out of 14 ER and PR positive cases 9 (64.2%) cases showing cyclin D1 positivity. There was significant correlation between cyclin D1 and hormones receptors (ER and PR). No significant correlation between cyclin D1and age, tumour grade and lymph node metastasis. Conclusions: Present study depicts significant correlation between cyclin D1 and hormones receptors (ER and PR). No significant correlation between cyclin D1and age, tumour grade and lymph node metastasis.